Beyond Deep Blue Chess in the Stratosphere - Newborn, Monty; SpringerLink (Online service). (London Springer London Imprint: Springer, 2011)
Morthan a decade has passed since IBM?s Deep Blue computer stunned the world by defeating Garry Kasparov, the world chess champion at that time. Following Deep Blue?s retirement, there has been a succession of better and better chess playing computers, or chess engines, and today there is little question that the world?s best engines are stronger at the game than the world?s best human players. Beyond Deep Blue: Chess in the Stratosphere tells the continuing story of the chess engine and its steady improvement from its victory over Garry Kasparov to ever-greater heights. The book provides analysis of the games alongside a detailed examination of the remarkable technological progress made by the engines ? asking the questions which one is best, how good is it, and how much better can it get. Presents a total of 118 games, played by 17 different chess engines, collected together for the first time in a single reference Details the processor speeds, memory sizes, and the number of processors used by each chess engine Reviews Deep Blue?s matches with Garry Kasparov in 1996 and 1997 Includes games from 10 World Computer Chess Championships, and the three most recent major computer chess tournaments of the Internet Chess Club Covers the man-machine matches between Fritz and Kramnik in 2002 and 2006, and between Kasparov and Deep Junior in 2003 Describes three historical matches between leading engines: Hydra versus Shredder, Junior versus Fritz, and Zappa versus Rybka This fascinating account of the ongoing evolution of computer chess will appeal to both the general reader and to specialists in A.I. and computing. Chess players and aficionados will also appreciate this remarkable insight into the new superstars of the classic game. Dr. Monty Newborn is an emeritus professor in the School of Computer Science at McGill University, Montreal, Canada. He is the author of the successful Springer titles Automated Theorem Proving: Theory and Practice and Deep Blue: An Artificial Intelligence Milestone.
Deep Blue Establishes Historic Landmark -- The Dawn of the Post Deep Blue Era -- 2002: Shredder Bows to Deep Junior at 10th WCCC -- 2002: Deep Fritz Befuddles Kramnik, Drawing 4-4 in Bahrain -- 2003: Deep Junior Confounds Kasparov, Drawing 3-3 in New York -- 2003: Shredder, the Comeback Kid, Comes Back at 11th WCCC -- 2004: Deep Junior Edges Out Shredder to Take 12th WCCC -- 2004: Hydra Slews Shredder in Abu Dhabi, 5-5?2.5 -- 2005: Zappa Red Hot at 13th WCCC -- 2006: Junior, Another Comeback Kid, Wins 14th WCCC -- 2006: Deep Fritz Clobbers Kramnik, 4?2 -- 2007: Deep Junior Deep Sixes Deep Fritz in Elista, 4?2 -- 2007: Rybka Moves to Top at 15th WCCC -- 2007: Zappa Upsets Rybka in Mexico City, 5.5?4.5 -- 2008: Rybka, Naum Top Field at Internet Chess Club CCT 10 -- 2008: Rybka Retains Title at 16th WCCC -- 2009: Rybka Tops at Internet Chess Club CCT 11 -- 2009: Rybka Rolls Through Opposition at 17th WCCC -- 2010: Sjeng Wins ICC CCT 12 -- 2010: Rybka Romps Again at 18th WCCC -- And Beyond Rybka.
Electronic reproduction.
Keywords: Computer science; Artificial intelligence; Computer chess; Deep Blue (Computer).